Restorative justice and probation decisions – an analysis of intentional assault cases in China - Lu, Hong (Psychology, crime & law, 2018)
The restorative justice model focuses on amending offender-victim relations. Compared to Western countries, China's criminal justice policy has relied on both formal and informal mechanisms in dealing with criminal offending. Recently a victim-offender reconciliation (VOR) program has been codified in China to provide incentives for offenders and victims to resolve their disputes through court-guided mediation sessions. Using restorative justice as an interpretive framework and drawing upon 1000 minor intentional assault cases, this study examines the impact of core VOR concepts on probation decisions. Our analysis suggests that offender compensation and attitude were significantly related to the likelihood of receiving probation, and the defense attorney played an unexpected yet impactful role in shaping judges’ probation decisions. Theoretical and policy implications are discussed.